Analysis of Organizational Psychology Perspective in Human Resource Management to Improve Job Satisfaction - Surianto, Surianto (Paradoks : Jurnal Ilmu Ekonomi, 2025)
This study examines the integration of organizational psychology perspectives into human resource management (HRM) to enhance job satisfaction. It examines the psychological factors that influence employee motivation, engagement, and well-being, highlighting the role of leadership, workplace culture, and HRM strategies in fostering a supportive and productive work environment. This study adopts a systematic literature review (SLR) approach, synthesizing findings from various disciplines related to HRM and organizational psychology. The research analyzes existing literature to identify key theoretical frameworks, best practices, and psychological insights contributing to job satisfaction. Sources were selected from reputable databases, including Elsevier, Emerald, Wiley, and Springer, to ensure the study's reliability and academic rigor. The findings highlight that motivational factors, such as autonomy, recognition, and career development, significantly contribute to job satisfaction. Additionally, leadership style plays a crucial role, as transformational leadership fosters higher motivation and engagement than transactional approaches. A positive organizational culture that promotes fairness, well-being, and inclusion enhances employee commitment and reduces turnover. The study further supports Herzberg's Two-Factor Theory, confirming the importance of both intrinsic and extrinsic factors in shaping job satisfaction. This study offers practical and managerial insights for organizations seeking to enhance their HRM strategies through psychological approaches. It suggests adopting employee-centered policies, including flexible work arrangements, well-being programs, and leadership development initiatives. Future research should focus on empirical validation and explore technology-driven HRM models in diverse industries.